The Effect of Principal Leadership, Financing, and Community Participation on the Effectiveness of Facilities and Infrastructure Management at Al-Khoir Islamic Boarding School - Denny Fitriani Hasibuan; Muhammad Fadhli (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study contains three objectives, including knowing the effect of principal leadership, financing, and community participation on the effectiveness of facilities and infrastructure management. This research method is quantitative. On the other hand, the use of sampling techniques is the Krinj and Morgan table of 45 respondents at Al-Khoir Islamic Boarding School. The data collection technique is a questionnaire. The results of the study interpreted that the principal's leadership variable had an influence (rho_a) of 0.622. Data analysis techniques using SmartPLS. While financing has an influence (rho_a) of 0.962. And community participation has an influence (rho_a) of 0.870 on the effectiveness of facilities and infrastructure management. Financing is the most dominant factor in this study. This implies that the success of facilities and infrastructure management in schools is highly dependent on how effectively funds are managed, allocated, and utilized to support operational activities and the development of educational facilities.